2020
DOI: 10.3389/fimmu.2020.578314
|View full text |Cite
|
Sign up to set email alerts
|

New Approaches for the Treatment of Chronic Graft-Versus-Host Disease: Current Status and Future Directions

Abstract: Chronic graft-versus-host disease (cGvHD) is a severe complication of allogeneic hematopoietic stem cell transplantation that affects various organs leading to a reduced quality of life. The condition often requires enduring immunosuppressive therapy, which can also lead to the development of severe side effects. Several approaches including small molecule inhibitors, antibodies, cytokines, and cellular therapies are now being developed for the treatment of cGvHD, and some of these therapies have been or are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 172 publications
0
63
0
1
Order By: Relevance
“…As NFκβ has long been known to play a critical role in T cell biology, particularly with respect to cytokine responses, it has always been an attractive target [40]. Several lines of evidence have recently suggested that inhibiting NFκβ signaling ameliorates GVHD in both mice and humans [41]. Bortezomib and PS-1145 are small molecule inhibitors that have been used to treat acute GVHD [42].…”
Section: Discussionmentioning
confidence: 99%
“…As NFκβ has long been known to play a critical role in T cell biology, particularly with respect to cytokine responses, it has always been an attractive target [40]. Several lines of evidence have recently suggested that inhibiting NFκβ signaling ameliorates GVHD in both mice and humans [41]. Bortezomib and PS-1145 are small molecule inhibitors that have been used to treat acute GVHD [42].…”
Section: Discussionmentioning
confidence: 99%
“…NFκB is a transcription factor that controls the expression of a number of genes important for mediating immune and inflammatory responses. Several lines of evidence have recently suggested that inhibiting NFκB signaling ameliorates GVHD in both mice and humans (53).…”
Section: Discussionmentioning
confidence: 99%
“…Further results of baricitinib therapy included decreased count of Th1 and Th2 cells, reduced expression of MHC and CD80/86 molecules, Treg cell expansion, and enhanced GVL effects 45 . These encouraging preclinical findings wait to be evaluated in human patients by a nonrandomized open‐label clinical trial aiming to evaluate JAK1/2 inhibition in chronic GVHD (NCT02759731) 46 …”
Section: Graft‐versus‐host Diseasementioning
confidence: 99%